(3JaSHjQ GdebGdGJ GdNeS ef cJGH OjGSbhQjOS GdYjf RQfi (B( (3GdCOhjI GdeaQOI (B)s - (3CHh OGhO SdjeGf Hf MSGf GdeYQha HGHf LdLds; (3OjGSbhQjOSs
(3ChdgG (B:s
(3GjQS (B: (3JChjdg ai GddSGf GdjhfGfi bhS bRM , hgh GdShSJ GdCSeGfLhfi ,hPdc Cf ai bQGQg HjGVkG s
(3BNQgG (B:s
(3djJhadG(B: (3JChjdg MLQ GdZQGA , hgh UeZ GdHdGW eYehd djKh MGhhS JChjdg GdMLQ GdCHjV s
(3Vef eLehY , JQJjHgG (B: (3ef U (B125 - (3U(B132s
(3GdeDda cGf MjkG SfI (B372(3g`s
(3GfXQ ebOeGJ GHf LdLd hWHbGJ GHf CHj CUjHYI (B48/2s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
GALS - (3GdLRA (B3 - (3U (B309 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B62 s
Keywords: (3GdWHs